FEASIBILITY ANALYSIS OF RAINFED RICE FARMING IN SERDANG MENANG VILLAGE SIRAH PULAU PADANG DISTRICT OKI REGENCY - Nur aisyah; Henny Rosmawati; Endang Lastinawati (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2026)
This study aims to analyze the income and feasibility of rainfed rice farming in Serdang Menang Village, Sirah Pulau Padang District, OKI Regency. This study used a survey method with a stratified disproportionate random sampling technique. The analysis was carried out through the income approach and RC ratio. The results showed that the income of rainfed rice farmers increased along with the increase in land area. The average income on narrow land was Rp5.714.699 lg/mt, medium land was Rp15.226.350 lg/mt, and large land was Rp52.084.000 lg/mt. While the RC ratio results on narrow land were 2.5, on medium land were 2.7, and on large land were 3.4, which means that all three lands are feasible to be cultivated. When compared between categories, land area showed the highest level of feasibility; the wider the land managed, the higher the income obtained and the more efficiently the farming business is run. Keywords: rainfed rice, income, farming feasibility, RC ratio